Development of Computer-Based Assessment Instruments Nuclear Physics Introduction Course as An Effort to Grade Authentically - Murniati; Sofia; Sudirman; Dwi Purnomo Aji (Postgraduate, University of Mataram, 2023)
The introductory course of nuclear physics in the physics education study program is carried out online, hybrid, and offline by providing teaching materials in the form of digital handouts equipped with videos to add explanations. The use of technology has been used as a learning evaluation tool, both to evaluate practice questions or official ones such as Quizizz, web-based, google form and form facade. This research is about the development of the Visscher-Voerman procedure which consists of Nature of analysis activities, Design (The shaping of the solution, Design (Media Selection), Design (Starting from target group instead of subject of matter), Evaluation (The use of formative evaluation) and Implementation and formative evaluation using Tessmer's evaluation stages: self-evaluation, expert review, one-to-one evaluation, small group evaluation and field test. The result of this research is a product in the form of a computer-based assessment instrument on nuclear physics introduction course that have met the validity criteria, reliable and practical, so that it can be used as a learning evaluation tool. The validity of the instrument was obtained from three lecturer reviewers in the content, construction, language and application sections with the respective results of 4.73 (very valid), 4.80 (very valid), 4.78 (very valid) and 4.58 (valid). Reliability of the instrument was tested with the help of SPSS version 22.0 for windows, by carried out simultaneously on all item items by looking at the Cronbach's alpha value for the midterm and final semester exams. The reliability results respectively are 0.82 with 25 items and 0.85 with 35 items included. It’s mean that they are in the reliable categories. Product practicality test was carried out on October 14 -15 2022 and continued on May 5 2023. The respondents are FKIP Physics UNSRI’s student class of 2019-2020, with one-to-one (3 students) trials, small group trials (10 students), and wide trials (36 students). The results are respectively 3.81, 3.89 and 3.72 with a very practical category.